2017
DOI: 10.3389/fimmu.2017.01391
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Clinical Effect of Diet Modulation of the Gut Microbiome in Multiple Sclerosis Patients: A Pilot Study

Abstract: Pathogenesis of autoimmune disorders, including multiple sclerosis (MS), has been linked to an alteration of the resident microbial commensal community and of the interplay between the microbiota and the immune system. Dietary components such as fiber, acting on microbiota composition, could, in principle, result in immune modulation and, thus, could be used to obtain beneficial outcomes for patients. We verified this hypothesis in a pilot study involving two groups of clinically similar relapsing-remitting (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
92
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 56 publications
8
92
0
2
Order By: Relevance
“…The Lachnospira belongs to the Lachnospiraceae family, which have a higher prevalence in multiple sclerosis patients following a high-vegetable/low-protein diet and are in accordance with previous data showing an increase of butyrate-producing bacteria in multiple sclerosis individuals after immunomodulatory treatment (Sushrut et al, 2016;Saresella et al, 2017). Martinez et al (2013) found whole grains increased the abundance of the genus Blautia, which is acetogenic and might benefit from the production of hydrogen, a product of glycan fermentation, and, therefore, likely induced by whole grain consumption (Nakamura et al, 2010;Koropatkin et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Lachnospira belongs to the Lachnospiraceae family, which have a higher prevalence in multiple sclerosis patients following a high-vegetable/low-protein diet and are in accordance with previous data showing an increase of butyrate-producing bacteria in multiple sclerosis individuals after immunomodulatory treatment (Sushrut et al, 2016;Saresella et al, 2017). Martinez et al (2013) found whole grains increased the abundance of the genus Blautia, which is acetogenic and might benefit from the production of hydrogen, a product of glycan fermentation, and, therefore, likely induced by whole grain consumption (Nakamura et al, 2010;Koropatkin et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The Lachnospira belongs to the Lachnospiraceae family, which have a higher prevalence in multiple sclerosis patients following a high‐vegetable/low‐protein diet and are in accordance with previous data showing an increase of butyrate‐producing bacteria in multiple sclerosis individuals after immunomodulatory treatment (Sushrut et al ., ; Saresella et al ., ). Martinez et al .…”
Section: Discussionmentioning
confidence: 97%
“…Although no differences are observed regarding beta diversity between treatments, the administration of Lactibiane iki, composed by genera Lactobacillus and Bifidobacterium, is associated with an increased abundance of the genus Lachnoclostridium (family Lachnospiraceae) and several taxa belonging to the family Bifidobacteriaceae, being this latter taxon consistent with probiotic composition itself. As previously mentioned, the family Lachnospiraceae has been previously associated with butyrate production and has also been correlated with IL-10 and TGF-β production by different immune cells [65]. Regarding Bifidobacteria, probiotics composed of different strains including Bifidobacterium have exhibited beneficial effects in EAE [11,69] and MS [17,18] and have been correlated with anti-inflammatory immune markers.…”
Section: Discussionmentioning
confidence: 82%
“…We also found that the clinical condition changes the global microbial community, a change explained partially by the increased abundance of taxa in the orders Clostridiales and Bacteroidales in the acute phase and in the orders Lactobacillales and Clostridiales in the chronic phase of EAE. The families Ruminococcaceae and Lachnospiraceae (order Clostridiales) and the family Bacteroidaceae (order Bacteroidales) have been described as highly prevalent in MS patients [65] and, together with taxa belonging to the family Rikenellaceae (order Bacteroidales), as also dominant in healthy individuals [66]. Members of these families have been previously associated with butyrate production, which is highly relevant because it promotes T reg cell differentiation and activity and ultimately suppresses pro-inflammatory responses [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many studies have linked such dysbiosis of the gut microbiome with both adult and pediatric MS disease incidence and prognosis (Camara‐Lemarroy, Metz, & Yong, ; Castillo‐Alvarez & Marzo‐Sola, ; Cekanaviciute et al, ; Cignarella et al, ; Kirby & Ochoa‐Reparaz, ; Libbey et al, ; Mangalam & Murray, ; Nourbakhsh et al, ; Ochoa‐Reparaz, Kirby, & Kasper, ; Tankou et al, ; Tremlett, Fadrosh, Faruqi, Hart, et al, ; Tremlett, Fadrosh, Faruqi, Zhu, et al, ; Tremlett & Waubant, ). Due to the presence of organized lymphoid structures, termed Peyer's patches, within the small intestine, a great deal of focus has been put on the influence of the gut microbiome on the immune pathology in MS. For instance, a pilot study including 20 patients with RRMS in Milan examined whether high vegetable, low protein (HV/LP) diet exhibited positive effects on MS disease course compared to a classical western diet through alterations in the gut microbiota (Saresella et al, ). In the HV/LP diet group, the Lachnospiraceae family was significantly more abundant in the gut microbiota, correlating with a significant decrease in IL‐17‐producing CD4+ T lymphocytes and PD‐1 expressing CD4+ T lymphocytes.…”
Section: Roles For Nutrition and Exercise In Cns Repairmentioning
confidence: 99%